2016
DOI: 10.1021/acsami.6b06157
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Ethylene Carbonate Electrolytes of Lithium Ion Batteries via Ring Opening Activated by LiCoO2 Cathode Surfaces and Electrolyte Species

Abstract: High-performance lithium-ion batteries require electrolytes that are stable over wide operating voltages. We used density functional theory to investigate the degradation of ethylene carbonate (EC) electrolytes activated by interactions with LiCoO cathode surfaces and PF species in the electrolyte. We report detailed mechanisms for the activation of EC ring-opening reactions by Lewis acids to form CO, organics, or organofluorines. We find that Lewis acid-base complexation between EC and either PF or LiCoO weak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
127
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(135 citation statements)
references
References 72 publications
6
127
2
Order By: Relevance
“…This is evidenced by X-ray photoelectron spectroscopy (XPS) and time-of-flight secondary ion mass spectrometry (TOF-SIMS) data collected on LCO and LCNO before and after 100 cycles in half-cell testing. [50] These features coherently suggest that on LCNO surface, side reactions including not only EC ring-opening but also PF 6 − , counterion of salt, to form PF 5 and HF, [51,52] are significantly suppressed. However, it decays to zero with an emerging peak at 532-533 eV (from O 1s orbital of oxidation products of electrolytes) for cycled LCO, while its intensity is better maintained in cycled LCNO.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…This is evidenced by X-ray photoelectron spectroscopy (XPS) and time-of-flight secondary ion mass spectrometry (TOF-SIMS) data collected on LCO and LCNO before and after 100 cycles in half-cell testing. [50] These features coherently suggest that on LCNO surface, side reactions including not only EC ring-opening but also PF 6 − , counterion of salt, to form PF 5 and HF, [51,52] are significantly suppressed. However, it decays to zero with an emerging peak at 532-533 eV (from O 1s orbital of oxidation products of electrolytes) for cycled LCO, while its intensity is better maintained in cycled LCNO.…”
Section: Resultsmentioning
confidence: 72%
“…In particular, one thing to note is that in C 1s region of cycled LCO, a dramatic increase of the C 1s peak characteristics of CO (C 1s, 286 eV) and CO (C 1s, 289 eV) bonds in ≈2:1 ratio upon cycling would be expected for mass generation of PEC, a result of ethylene carbonate (EC) decomposition (Figure 4f). [50] These features coherently suggest that on LCNO surface, side reactions including not only EC ring-opening but also PF 6 − , counterion of salt, to form PF 5 and HF, [51,52] are significantly suppressed. As illustrated in Figure 4g, consistent trend is also found in TOF-SIMS mapping, showing less accumulation of CEIs species (e.g., 7 LiF 2 − , C 3 OF − , CoF 3 − , CH 3 O − , C 2 HO − , and C 2 F − from electrolyte decomposition) [53,54] on the surface of LCNO than that of LCO (for more details, see Figures S22 and S23 and Table S6, Supporting Information).…”
Section: Resultsmentioning
confidence: 72%
“…S4 in our Supporting Information (SI) Section 2 for the detailed information about the atomistic structure of the initial state in the work of Tebbe, et al 24 . For our NMC, we compared the energy between the configuration of the EC adsorption at two neighboring transition metal reported in the 1 1 work of Tebbe, et al 24 and the configurations of the intermediate states #0, #2 and #4 shown in Fig. 3(a) of the present work.…”
Section: Reaction Energy Barriers Of the Ec Ring-opening Process Undementioning
confidence: 99%
“…The energy of the bonding configurations involving two neighboring transition metal centers is 40 meV lower than the energy of state #0, 95 meV higher than the energy of state #2 and 210 meV higher than the energy of state #4 in our NMC cathode surface case. Moreover, the reported energy barriers of the EC bond breaking (ethylene carbon and ethylene oxygen bond C E -O E ) processes in the work of Tebbe, et al 24 are all larger than 1 eV, while the calculated reaction energy barrier in our modeled pathway is only 290 meV. Therefore, aside from the predicted reaction pathway reported by Tebbe, et al 24 , the reaction pathway studied in this work is also a kinetically and thermodynamically feasible mechanism for the EC molecule bond breaking process as the initial step in it complete decomposition reaction.…”
Section: Reaction Energy Barriers Of the Ec Ring-opening Process Undementioning
confidence: 99%
“…So far we have focused on flat Li x CoO 2 (104) surfaces. Other models, in which (104) surfaces are covered with CoOH groups due to reaction with H 2 O in the atmosphere, have been proposed [70]. Fig.…”
Section: Explicit Interfacementioning
confidence: 99%